2006
DOI: 10.1111/j.1462-5822.2006.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Botrytis cinerea virulence is drastically reduced after disruption of chitin synthase class III gene (Bcchs3a)

Abstract: SummaryBotrytis cinerea is an important phytopathogenic fungus requiring new methods of control. Chitin biosynthesis, which involves seven classes of chitin synthases, could be an attractive target. A fragment encoding one of the class III enzymes was used to disrupt the corresponding Bcchs3a gene in the B. cinerea genome. The resulting mutant exhibited a 39% reduction in its chitin content and an 89% reduction in its in vitro chitin synthase activity, compared with the wild-type strain. Bcchs3a mutant was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 50 publications
2
55
0
Order By: Relevance
“…1B to F, arrowheads). These extracellular structures were similar to those observed in the class III chitin synthase mutant of Botrytis cinerea (40). Vesicles with electron dense contents were frequently seen in ⌬B-18 (Fig.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…1B to F, arrowheads). These extracellular structures were similar to those observed in the class III chitin synthase mutant of Botrytis cinerea (40). Vesicles with electron dense contents were frequently seen in ⌬B-18 (Fig.…”
Section: Resultssupporting
confidence: 60%
“…Class III chitin synthases have been reported to be involved in the virulence of some pathogens. Deletion of Bcchs3a in the phytopathogenic fungus Botrytis cinerea and double deletion of WdCHS3 and class I chitin synthase WdCHS2 in the human pathogen Wangiella dermatitidis both caused a reduction of virulence (40,48). On the other hand, the deletion mutant of a class III chitin synthase-encoding gene, CgChsIII, of the maize pathogen Colletotrichum graminicola did not exhibit the significant phenotypic difference from the wild-type strain (50).…”
mentioning
confidence: 99%
“…We cannot exclude the possibility that this effect is due to the impaired cell wall integrity of Bccrz1 mutants, since bmp3 mutants (loss of cell wall integrity MAP kinase) were also defective in mycelium-derived infection (data not shown), while spores were still able to infect the plant (54). Moreover, B. cinerea chitin synthase (Bcchs1 or Bcchs3a) mutants exhibiting reduced chitin contents in their cell walls were also shown to be affected in virulence (66,67). The fact that Mg 2ϩ supplementation improved the cell wall stability and penetration rates of Bccrz1 mutants indicates the importance of intact cell walls for normal infection efficiencies.…”
Section: Bccrz1 Acts As a Downstream Target Of (Yeast) Calcineurinmentioning
confidence: 97%
“…On the other hand, it was shown that disruption of only one CHS gene could lead to a drastic reduction in the pathogenicity of plant parasites (53,74,86,88), suggesting that targeting only one enzyme might be sufficient. Apparently, there are fewer CHS genes in oomycetes than in fungi.…”
Section: Vol 7 2008 Aphanomyces Euteiches Cell Wall Chitosaccharidementioning
confidence: 99%